(untitled) (International Seven Journal of Health Research, 2024)
Acute aortic dissection (AAD) is a clinical condition with an obscure prognosis, possibly fatal evolution and complicated diagnosis. Among the diseases that cause chest pain, the diagnosis of AAD is usually one of the least speculated, and the aid of imaging tests is often necessary to raise this hypothesis. The present case report aims to describe the clinical condition of admission and the therapeutic approach adopted in a patient who was admitted to the emergency department complaining of severe chest pain, radiating to the jaw. The initial suspicion was AMI, and catheterization was instituted, which did not show any coronary obstruction. Chest X-ray raised suspicion of AAD, which was confirmed with a CT angiography. Although she received an incorrect diagnosis at first, the patient was correctly submitted to the procedures and received appropriate treatment, having survived the acute condition of aortic dissection.